Resepsi Hadis Tuntunan Sebelum dan Setelah Pernikahan Dalam Film Papi dan Kacung Episode 12-13 - Nurmansyah, Ihsan (UIN Sunan Kalijaga Yogyakarta, 2019)
This paper discusses the study of living hadith in the film “Papi dan Kacung” (read: PdK) episodes 12-13 uploaded by Qoryyan on Instagram in 2019. The film is a short film of Islamic nuances which in each scene shows a reception of the Prophet’s hadith, especially about guidance before and after marriage. In addition, one of the episodes of the film has received more comments from Instagram account users compared to other episodes. Therefore, to find out the variety of receptions on the Prophet’s hadith in the film “PdK” episodes 12-13 using reception theory introduced by Ahmad Rafiq. The results of this study are 1) exegetical reception manifested in the reading of the Book Riyadhus Shalihin and Minhajul Muslim: Konsep Hidup Ideal dalam Islam; 2) the aesthetic reception contained in the reading of the two hadith books accompanied by the backsound